2021
DOI: 10.1186/s12933-021-01357-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic mechanistic profile of patients with diabetes at risk of developing heart failure: insights from the HOMAGE trial

Abstract: Background Patients with diabetes mellitus (DM) are at increased risk of developing heart failure (HF). The “Heart OMics in AGEing” (HOMAGE) trial suggested that spironolactone had beneficial effect on fibrosis and cardiac remodelling in an at risk population, potentially slowing the progression towards HF. We compared the proteomic profile of patients with and without diabetes among patients at risk for HF in the HOMAGE trial. Methods Protein biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Furthermore, another study of women with gestational diabetes found an overexpression of Gal-4 in the placental syncytiotrophoblast cells, compared to healthy controls [ 35 ]. Thus, one proposed explanation for our main finding may be Gal-4’s involvement in the development of diabetes, which also has been suggested in a previous publication with a similar approach of proteomic exploration [ 36 ]. To elucidate this, we carried out a post-hoc analysis, suggesting that elevation in Gal-4 was associated with higher probability of being HO only in those with prevalent diabetes.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, another study of women with gestational diabetes found an overexpression of Gal-4 in the placental syncytiotrophoblast cells, compared to healthy controls [ 35 ]. Thus, one proposed explanation for our main finding may be Gal-4’s involvement in the development of diabetes, which also has been suggested in a previous publication with a similar approach of proteomic exploration [ 36 ]. To elucidate this, we carried out a post-hoc analysis, suggesting that elevation in Gal-4 was associated with higher probability of being HO only in those with prevalent diabetes.…”
Section: Discussionsupporting
confidence: 67%
“…As detailed earlier, the proteomic studies from the HOMAGE trial were able to show changes in proteomic biomarkers in response to MRA treatment in patients at risk of HF. Verdonschot et al used a similar approach to show differential expression of plasma proteins in patients at risk of HF with/without diabetes (Verdonschot et al 2021). In diabetic patients, the plasma concentration of COL1A1 and PICP decreased, and plasma concentration of MMP7 increased after 9 months of spironolactone treatment (Verdonschot et al 2021).…”
Section: Approach To Identifying Novel Blood-based Biomarkers Of the ...mentioning
confidence: 99%
“…Verdonschot et al used a similar approach to show differential expression of plasma proteins in patients at risk of HF with/without diabetes (Verdonschot et al 2021). In diabetic patients, the plasma concentration of COL1A1 and PICP decreased, and plasma concentration of MMP7 increased after 9 months of spironolactone treatment (Verdonschot et al 2021). Another study to employ the use of high-throughput proteomic profiling is the ongoing MyoVasc study; a large, prospective, observational cohort study aiming to use multi-omics profiling to gain a better understanding of HF pathophysiology (Gobel et al 2021).…”
Section: Approach To Identifying Novel Blood-based Biomarkers Of the ...mentioning
confidence: 99%
“…In order to resolve the controversy, we utilized a new proteomic assay platform—Olink proximity extension assay, which has been widely applied in the biomarker discovery of the cardiovascular disease field ( 16 , 17 ), to assess the change in 181 different proteins during the acute post-procedure phase from the cryoballoon ablation group and irrigated-tip RF catheter ablation group. We also introduced the RB ablation group into comparison to avoid alteration resulting from lesion size rather than energy sources ( 18 ).…”
Section: Introductionmentioning
confidence: 99%